ANALISIS PENDIDIKAN DIGITAL DALAM KEBIJAKAN DAN REGULASI DI INDONESIA - Ahmad Maulana; Abdur Rakib; Afipudin Abdul Jalil; Andi Warisno; Nila Wati Tajudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology has driven transformation in various areas of life, including education. Digital education is one strategy to improve the quality, accessibility, effectiveness, and equity of educational services. Its implementation requires clear regulations and policies as a foundation for managing the use of digital technology in a targeted, safe, and sustainable manner. Digital education regulations serve as guidelines for implementing technology-based learning, personal data protection, cybersecurity, digital infrastructure management, and educational quality assurance. Meanwhile, digital education policies play a role in determining the direction, objectives, strategies, and programs that support digital transformation in the educational environment. Digital education policies and regulations involve various stakeholders, including the government, educational institutions, educators, students, and the community. The government plays a role in formulating regulations, providing infrastructure, improving human resource competency, and overseeing implementation. At the educational institution level, policy implementation is carried out through the use of digital platforms in the learning process, administration, evaluation, and student competency development. However, the implementation of digital education still faces various challenges, such as disparities in technology access, limited digital literacy, data security, and human resource readiness.